3478 Knowledge, Attitudes and Practices on End-of-Life Care among Healthcare Professionals in a Community Hospital in Puerto Rico - Deana Hallman; Ivonne Jimenez (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: The study aims to determine the baseline knowledge, attitudes and practices of the professionals (i.e., doctors and nurses) that provide the end-of-life care at an acute community hospital. By obtaining information on what is known, what is believed and what is done by doctors and nurses in end-of-life care, we can identify needs, problems, barriers and possible solutions. METHODS/STUDY POPULATION:. Develop a questionnaire in Spanish addressing knowledge, attitudes and practices about end-of-life care in an acute hospital, define the survey objectives, and develop the survey protocol. o To validate the pertinence and usefulness of each questionnaire item, a panel of experts in palliative and end-of-life care will be consulted. o To finalize the questionnaire, it will be pre-tested with a small number of healthcare providers randomly selected from the survey’s intended population. Implement the questionnaire to doctors/nurses providing direct end-of-life care by purposeful sampling at an acute community hospital. o Beforehand, survey interviewers will be recruited and trained. Perform quantitate and qualitative analyses o Answers to closed-end questions and quantitative data will be tallied using Microsoft Excel and analyzed using STATA statistical software. o Relationship between the participant’s characteristics and their knowledge, attitudes and practices will be assessed using chi-square test. o Answers to open-ended questions in the questionnaire will be collected, analyzed based on their content, and placed in more comprehensive categories by NVivo software. RESULTS/ANTICIPATED RESULTS: It is expected to capture variations and/or consistencies in the amount of knowledge, the type of attitudes and the actual practices among and within physicians and nurses on end-of-life care in a community acute hospital. DISCUSSION/SIGNIFICANCE OF IMPACT: The proposed research is expected to contribute key information from the perspectives of physicians and nurses who deliver end-of-life care in an acute community hospital in Puerto Rico. This contribution is significant because it will serve as the platform to develop culturally-appropriate educational/training materials and, subsequently, implement culturally-responsive guidelines for the care of seriously ill Hispanics, with the expectation of improving their quality of life, and perhaps reducing their medical care costs.